Підтримка бізнесу в Україні під час війни - Чемеренко, А. А. (ХНУРЕ, 2024)
This work analyzes business support in Ukraine. What problems faced the business before the full-scale invasion. Understands how the war affected the business situation as a whole. The importance of business support for the economy of Ukraine. How the government helps to strengthen the economy of the country through the support of entrepreneurs. It tells about grants operating in Ukraine, from the government and investors, and how their introduction affects business and the country's economy as a whole. Analyzes what expectations the Ukrainian government has for the further development of business in Ukraine
Keywords: підтримка бізнесу; бізнес під час війни